Regulation of phosphatidylglycerolphosphate synthase in Saccharomyces cerevisiae by factors affecting mitochondrial development. - Gaynor, P M (1991)
Phosphatidylglycerolphosphate synthase (PGPS; CDP-diacylglycerol glycerol 3-phosphate 3-phosphatidyltransferase; EC 2.7.8.5) catalyzes the first step in the synthesis of cardiolipin, an acidic phospholipid found in the mitochondrial inner membrane. In the yeast Saccharomyces cerevisiae, PGPS expression is coordinately regulated with general phospholipid synthesis and is repressed when cells are grown in the presence of the phospholipid precursor inositol (M. L. Greenberg, S. Hubbell, and C. Lam, Mol. Cell. Biol. 8:4773-4779, 1988). In this study, we examined the regulation of PGPS in growth conditions affecting mitochondrial development (carbon source, growth stage, and oxygen availability) and in strains with genetic lesions affecting mitochondrial function. PGPS derepressed two- to threefold when cells were grown in a nonfermentable carbon source (glycerol-ethanol), and this derepression was independent of the presence of inositol. PGPS derepressed two- to fourfold as cells entered the stationary phase of growth. Stationary-phase derepression occurred in both glucose- and glycerol-ethanol-grown cells and was slightly greater in cells grown in the presence of inositol and choline. PGPS expression in mitochondria was not affected when cells were grown in the absence of oxygen. In mutants lacking mitochondrial DNA [( rho0] mutants), PGPS activity was 30 to 70% less than in isogenic [rho+] strains. PGPS activity in [rho0] strains was subject to inositol-mediated repression. PGPS activity in [rho0] cell extracts was derepressed twofold as the [rho0] cells entered the stationary phase of growth. No growth phase derepression was observed in mitochondrial extracts of the [rho0] cells. Relative cardiolipin content increased in glycerol-ethanol-grown cells but was not affected by growth stage or by growth in the presence of the phospholipid precursors inositol and choline. These results demonstrate that (i) PGPS expression is regulated by factors affecting mitochondrial development; (ii) regulation of PGPS by these factors is independent of cross-pathway control; and (iii) PGPS expression is never fully repressed, even during anaerobic growth.